ANALISIS PERSEPSI MASYARAKAT DUNIA TERHADAP VIRTUAL YOUTUBER YANG MENAWARKAN PENGALAMAN KEKASIH - Muhammad Haikal; Bagus Prayogi; Nathanael Putra Ganatha; Muhammad Rivan Ferdiansyah; Nur Aini Rivan Rakhmawati (E-Link: Jurnal Teknik Elektro dan Informatika, 2024)
This research investigates the global public's perception of the phenomenon of Virtual YouTubers (VTubers) who offer romantic experiences such as "boyfriend" or "girlfriend experience." Involving sentiment analysis, this study collected and classified 1623 comments from social media platforms using the Microsoft Azure algorithm. The analysis results indicate that the majority of the public holds a negative view of such relationships, depicting the complexity of social interactions in the digital world. These findings underscore the importance of understanding the impact of VTubers' phenomenon in the context of parasocial relationships. The research recommends increased discussions through other social platforms and the development of more advanced sentiment analysis models for a deeper understanding of this phenomenon. The research findings emphasize the relevance and complexity of VTubers' phenomenon in today's digital culture, highlighting the importance of developing social understanding of human interactions in a virtual context.